Motor Habits in Visuo-manual Tracking: Manifestation of an Unconscious Short-Term Motor Memory? - Andreas Hufschmidt; Günther Deuschl; Carl Hermann Locking (Behavioural Neurology)
Normal subjects were tested in short, repetitive trials of a tracking task, with an identical shape of target movement being used throughout one session. Analysis of the net error curves (pursuit minus target movement) revealed that subjects regularly exhibit a remoteness effect: neighbouring trials were more similar than distant ones. The effect is demonstrated to be stronger in the absence of visual cues, and was found to be absent in a patient with complete loss of proprioception when he was performing without visual feedback as well. The results are discussed in terms of a short term memory store contributing to unconscious movement habits in tracking. This may represent part of the motor learning process working together with conscious visuo-motor control mechanisms. Its function is probably related to the acquisition of automatic movements.